Types of silvopastoral systems: adding trees to pastoral/rangelands. - Beltran, Marcelo Javier; Cambareri, Gustavo Sebastián; Banegas, Natalia Romina; Peri, Pablo Luis; Colcombet, Luis; Martínez Pastur, Guillermo; Lencinas, Maria Vanessa; Rodríguez Souilla, J.; Cellini, Juan Manuel; Cosentino, Vanina Rosa Noemi (Burleigh Dodds Science, 2025)
Silvopastoral Systems (SPS) have been identified as an efficient land management strategy to increase the performance of animal and tree production, livestock welfare (Esquivel, 2017), and improve carbon (C) sequestration in soil and in trees to offset livestock emissions (Figueiredo et al., 2017). These systems are a type of livestock agroforestry, which associates trees and/or shrubs with pastures (Mosquera-Losada et al., 2006; Chará et al., 2020). The system comprises a woody component, which involves any type of tree, interacting with conventional components (herbaceous forage or pastures) under an integrated management system (Gándara et al., 2021). Trees provide timber, fruit, firewood, seeds, and shade generators (Luccerini et al., 2013). SPS are alternative management systems which both mitigate and adapt to climate change (Feliciano et al., 2018). SPS are a sustainable way of land management that has been both politically and economically promoted worldwide (CAP 2014–2020) as a tool to increase carbon sequestration in soils among other benefits that agroforestry provides (Mosquera-Losada et al., 2018). In SPS, there are both ecological and economic interactions between the different components. Thus, SPS are those that have been designed to improve beneficial–ecological interactions, which may be shown as improvement in yield per unit area, resource use efficiency, and/or enhancement in environmental issues. Silvopastoral advantages can be enumerated as the provision of multiple products (e.g. food, wood, fodder, mulch, medicinal plants) or services (e.g. maintenance of soil fertility, erosion control, microclimate improvement, biodiversity enhancement, watershed protection, reduction of fire risk, carbon sequestration) by the trees (Peri et al., 2016a; Mosquera-Losada et al., 2005). In some regions or areas, SPS are used according to the basic premise that these systems can be more biologically productive, profitable, and sustainable than forestry or animal production monocultures depending on the environment. The trees in SPS enhance nutrient uptake from the soil, which is then returning to the grass through the degradation of organic matter, improving both soil fertility and forage quality. The trees, furthermore, strengthen animal welfare due to their moderating effects on climate extremes (Dube et al., 2012; Peri, 2011).